Komunitas Islam di Prancis - Misbahuddin Misbahuddin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2009)
The presence of moslem in France became important on modern era with North Africa colonization started in 1830. Hucksters who were so called turco arrived from Algeria after the year 1850. After this century, immigrant from Algerian and Maroko arrived in France to work at Marseilles shipyard, France Metro construction, and North France mining. France is a pluralistic state as other states in the world since there are several religions in it. The majority of its residents are Catholic while parts of them are Protestant. This pluralistic condition in turn becomes a concerned problem in France. Despite of this problem, Islam becomes the second biggest religion after Christian.